The Effect of Slice Thickness on the Volume Estimations Performed by Using Cone Beam CT - Seval Bayrak; Omer Said Sezgin; Saadettin Kayıpmaz; Gamze Çan (Cumhuriyet University, 2018)
Objective: The purpose of this study is to investigate possible effects of the slice thickness on volume estimations with CBCT.   Materials and Methods: Intraosseous cavities representing bone defects on femoral condyles of bovines were scanned by CBCT. Consecutive slices at 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, and 5 mm thickness were used to estimate the volumes of the cavities using Cavalieri principle of stereological methods then compared with the volumes obtained by Archimedean principle.   Results: The volumes estimated by Cavalieri principle in 0.1, 0.2, and 0.3 mm thickness slices were consistent with the volumes obtained by Archimedean principle (p>0.05). For all the defects on the CBCT images, the volumes of the defects which were calculated with Cavalieri principle in 0.1, 0.2, and 0.3mm slice thickness were found to be consistent with the actual volumes, however, the volumes that were calculated in 0.4 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4mm, and 5 mm slice thickness were found to differ from the actual volumes.   Conclusion: When volume calculations were made by Cavalieri principle, the thinnest slice section should be chosen to make calculations consistent with actual volumes.